Rent Control and Tenure Duration in Ethiopia: Reflections on the New Residential Housing Rent Control and Administration Law - Habtamu Sitotaw Semahagne; Alelegn Wenedem Agegnehu (Mizan law review, 2025)
This article examines rent control and tenure duration in Ethiopia, focusing on the Residential Housing Rent Control and Administration Proclamation No. 1320/2024 through a review of laws and the literature. The different regimes in Ethiopia have been regulating residential housing rent and tenure. Proclamation No. 1320/2024, enacted in April 2024, extends previous legal practices in Addis Ababa and other major cities. The law has implications for modernizing the housing rent system and improving tax collection. However, the law adversely affects the property rights of house owners and the principle of freedom of contract. It may encourage informal rental agreements and unofficial payments and may contribute to a shortage in residential rental housing. The article argues for a reduced government role in regulating the residential housing sector and underscores the importance of respecting contractual freedom. It calls for improved land delivery for housing, the adoption of a standardized, expert-driven valuation system, and further digitization of the sector.